Natural products targeting the synthesis of β(1,3)-D-glucan and chitin of the fungal cell wall. Existing drugs and recent findings - (:unkn) unknown (Elsevier, 2021)
Background: During the last three decades systemic fungal infections associated to immunosuppressive therapies have become a serious healthcare problem. Clinical development of new antifungals is an urgent requirement. Since fungal but not mammalian cells are encased in a carbohydrate-containing cell wall, which is required for the growth and viability of fungi, the inhibition of cell wall synthesizing machinery, such as β(1,3)-D-glucan synthases (GS) and chitin synthases (CS) that catalyze the synthesis of β(1-3)-D-glucan and chitin, respectively, represent an ideal mode of action of antifungal agents. Although the echinocandins anidulafungin, caspofungin and micafungin are clinically well-established GS inhibitors for the treatment of invasive fungal infections, much effort must still be made to identify inhibitors of other enzymes and processes involved in the synthesis of the fungal cell wall. Purpose: Since natural products (NPs) have been the source of several antifungals in clinical use and also have provided important scaffolds for the development of semisynthetic analogues, this review was devoted to investigate the advances made to date in the discovery of NPs from plants that showed capacity of inhibiting cell wall synthesis targets. The chemical characterization, specific target, discovery process, along with the stage of development are provided here. Methods: An extensive systematic search for NPs against the cell wall was performed considering all the articles published until the end of 2020 through the following scientific databases: NCBI PubMed, Scopus and Google Scholar and using the combination of the terms “natural antifungals” and “plant extracts” with “fungal cell wall”. Results: The first part of this review introduces the state of the art of the structure and biosynthesis of the fungal cell wall and considers exclusively those naturally produced GS antifungals that have given rise to both existing semisynthetic approved drugs and those derivatives currently in clinical trials. According to their chemical structure, natural GS inhibitors can be classified as 1) cyclic lipopeptides, 2) glycolipids and 3) acidic terpenoids. We also included nikkomycins and polyoxins, NPs that inhibit the CS, which have traditionally been considered good candidates for antifungal drug development but have finally been discarded after enduring unsuccessful clinical trials. Finally, the review focuses in the most recent findings about the growing field of plant-derived molecules and extracts that exhibit activity against the fungal cell wall. Thus, this search yielded sixteen articles, nine of which deal with pure compounds and seven with plant extracts or fractions with proven activity against the fungal cell wall. Regarding the mechanism of action, seven (44%) produced GS inhibition while five (31%) inhibited CS. Some of them (56%) interfered with other components of the cell wall. Most of the analyzed articles refer to tests carried out in vitro and therefore are in early stages of development.
Keywords: Systemic fungal infection; Fungal cell wall; Cell wall synthases; Bioactive natural products; Plant extracts; Antifungal drugs